2011
DOI: 10.4136/ambi-agua.175
|View full text |Cite
|
Sign up to set email alerts
|

Remoção de nutrientes por Typha latifolia e Cynodon spp. cultivadas em sistemas alagados construídos

Abstract: Objetivou-se, neste trabalho, avaliar a capacidade extratora de duas espécies vegetais quando cultivadas em sistemas alagados construídos de escoamento subsuperficial horizontal (SACs) para o tratamento das águas residuárias da suinocultura (ARS). Para tal, foram construídos 8 SACs de 2,0 m x 0,5 m x 0,6 m, em fibra de vidro, preenchidos com 0,55 m de brita zero. Nos SAC 2 ; SAC 4 ; SAC 6 e SAC 8, foi cultivada a taboa (Typha latifolia) e nos SAC 3 ; SAC 5 ; SAC 7 e SAC 9 foi cultivado o capim tifton-85 (Cynod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
18

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 14 publications
(27 reference statements)
1
7
1
18
Order By: Relevance
“…The extraction values observed in this study were similar to those observed by MATOS et al (2009) andFIA et al (2011). The extractions are influenced by amounts applied to the systems and by environmental conditions imposed on plants.…”
Section: Micronutrient Removalsupporting
confidence: 72%
See 3 more Smart Citations
“…The extraction values observed in this study were similar to those observed by MATOS et al (2009) andFIA et al (2011). The extractions are influenced by amounts applied to the systems and by environmental conditions imposed on plants.…”
Section: Micronutrient Removalsupporting
confidence: 72%
“…Reports in the literature point to the fact that the absorption of pollutants by vegetation cannot singlehandedly answer for the high efficiencies of pollutant removal (BRAZIL et al, 2007;FIA et al, 2008;FIA, 2009;KANTAWANICHKUL et al, 2009;MATOS et al, 2009;FIA et al, 2011). This fact calls into question the role of macrophytes in these systems, and there is no consensus among researchers about the actual importance of macrophytes in CWSs (Brix, 1997).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…After the first cut, 60 days after planting, a statistical difference was observed between SW dosages and conventional chemical fertilization (AQT0), as seen in In a study with constructed wetland systems (CWs), Fia et al (2011) concluded that Tifton 85 grass removed about 450 kg ha -1 of TKN and 100 kg ha -1 of P in two cuts after 120 days of cultivation. Fia et al (2014) found that Tifton 85 grass was able to extract between 9.8 and 17.6 kg ha -1 d -1 of TKN and between 0.6 and 1.7 kg ha -1 d -1 of PT, which represented 4.6 and 5.4% of the TKN and PT, respectively, contributed to the system.…”
Section: Extraction Of Nutrients By Tifton 85 Grassmentioning
confidence: 99%